Type specimens preserved in the Trèmols and Costa herbaria (BC) - Laura Gavioli; Neus Ibáñez; Ignasi Soriano (Anales del Jardín Botánico de Madrid, 2016)
The Trèmols herbarium, preserved at the Botanical Institute of Barcelona, is one of the oldest herbaria in Catalonia, largely made up of European plants collected in 19th century. The digitization of this historical collection, currently in progress, has made possible to locate nomenclatural types of various authors, acquired through exchange. In this article, we indicate two syntypes (for Fumaria caespitosa Loscos and Carex loscosii Lange), and one isolectotype (Polygala vayredae Costa) in Trèmols herbarium. Additionally, we designate the lectotype of Polygala vayredae in the Costa herbarium and its isolectotype in the Vayreda herbarium.